Aneuploidy Analysis of 5740 Referral Cases: A Triennial Report - Shah, Nidhi P.; Shah, Parth S.; Bhatt, Nirzari H.; Vaghasia, Ketan K.; Mistry, Krishna; Dominic, Jeanny; Shah, Sandip C.; Rao, Mandava V. (International Journal of Innovative Research in Medical Science, 2020)
Background and Objectives: Aneuploidy is one of the major concerns to cause genetic anomalies. This condition is mostly related to addition and/or deletion with respect to set(s) of chromosomes. Here, we report an analysis of 5740 referral cases during three consecutive years (2015 – 2018) from our Diagnostic Research Center, Ahmedabad for aneuploidy pattern. Methodologies: The patients were asked to fill the necessary forms and their blood (5ml) was drawn for chromosomal studies using the Karyotyping following International System for Human Cytogenetic Nomenclature (ISCN) manual. Results: The data revealed the numerical aberrations for only aneuploidy detected was (3.7%; 211/5740). In this report, constitutional (c) autosomal aneuploidy was 75% (158/211). The total mosaic cases were nine (9/211) comprising constitutive (2) and acquired (7) aneuploidy cases. In autosomal aneuploidy, cT21 was higher (96%; 152/158) than others (4%; 6/158) comparatively. Among cT21 (152), males (76%; 115/152) were more affected than females (24%; 37/152). These statistical data also revealed that acquired chromosomal aneuploidy (leukemia) possessed (25%; 53/211); with more mosaic cases (7/211). Conclusion: Couples with such conditions are eligible for genetic tests and counseling as well as new strategies are urgently to be undertaken by governmental organizations (GOs) and non-governmental organizations (NGOs) for affected families with better personalized and informed decision making. The significance of these data is thus discussed in relation to genetic disorders caused by constitutional and acquired aneuploidy of leukemic blood in this report.